Análise técnica, legal e social para subsídios à outorga de direito de uso dos recursos hídricos na bacia hidrográfica do rio Ibicuí - RS - Ravanello, Mariane Moreira (2007)
The grant of water use is an instrument of the Brazilian Water Resources Policy that must be analyzed according to its legal, technician and social character. Concerning the legal character, the grant process structure must attend the current law; as regards the technique questions, the process assessment passes for the balance of water availability and demand; the social character is attended in the analysis of the preferential water uses in the river basin, to be definite by the population and considered in the balance calculation. The objective of the present research is the procedural improvement of water balance for grant, considering in an articulated manner in the technician, legal and social and aspects and the interaction between basins of rivers with different domains. The Ibicuí river basin, object of study, is characterized by the intense water use for irrigation of the rice cultivation. The basin has two well characterized conditions of contour: one in upstream, defined for the Santa Maria basin river, and other, downstream next to the outfall in the Uruguay river (river of national domain). The water balance is made with the aid of two decision support tools: the models CRUZ and OutorgaLS. The applicability of the models in solution of problems of grant for the study area is analyzed, considering the months of irrigation (November to February) of years whose water offers is equal to the lower limit of the reliable interval of 90% (dry years). The results, although different, demonstrate that the two models can be used for the formulation of scenes. These differences are based on the models characteristics, that possess different ways of presentation, but result in analysis of same trend. A social prospection, with questionnaire use, was ccomplished with the aim to get a vision of the society regarding the questions related to water resources. Moreover, the questionnaire served as spreading of the National System of Water Resources, since that, during the application, people had demonstrated interest in knowing the responsible by decision in the basin. As conclusion, it is observed that it is possible to use the models of integrated manner, using the best characteristics of both. The OutorgaLS model reveals adequate for simulation between different types of use, therefore, for users of same priority, the optimization model can not converge. In this case, for users of same type of use, the model CRUZ gets to optimize the water balance, to consider the ambient reserve and also to propose rationings.